2020
DOI: 10.1111/clr.13672
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiographic outcomes of implant‐supported fixed dental prostheses with cantilever extension. A retrospective cohort study with a follow‐up of at least 10 years

Abstract: Aim: To report the clinical and radiographic outcomes of implant-supported fixed dental prostheses with cantilever extensions (FDPCs) after a function time ≥10 years. Material and methods: Patients with FDPCs in posterior areas were clinically and radiographically re-evaluated. Mesial and distal radiographic marginal bone levels (mBLs) from baseline (i.e. delivery of FDPC) to the follow-up examination were calculated and compared between implant surfaces adjacent to and distant from the cantilever extension. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…Finally, delivery of SCs with cantilever extension in posterior areas reduced treatment time, costs and patient's morbidity by avoiding the need for more invasive surgical interventions such as lateral sinus floor elevations or vertical bone augmentations 17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, delivery of SCs with cantilever extension in posterior areas reduced treatment time, costs and patient's morbidity by avoiding the need for more invasive surgical interventions such as lateral sinus floor elevations or vertical bone augmentations 17 …”
Section: Discussionmentioning
confidence: 99%
“…Outcomes from prospective and retrospective clinical studies of implant have been published, with follow‐up periods of 5 years or less 13‐18 …”
Section: Introductionmentioning
confidence: 99%
“…In the present study, an increase in shear stress in the cortical bone of 10.81% was obtained in the experimental group, in the cervical region of the implant near the first threads, and in the medullary bone of 12.29%, which may suggest an increased risk of osseointegration loss in poorly positioned implants (Figure 3.d,3.e 3.f). Schmid et al (2020) and Zurdo et al (2009) reported that bone loss tends to increase in cantilever-associated implants, however Hasan et al (2014) stated that although there is maximization of stresses in cancellous bone under functional loading, greater importance should be given to the bone thickness in which the implant will be installed.…”
Section: Discussionmentioning
confidence: 99%
“…According to Zurdo et al (2009), Schmid et al (2020), Papaspyridakos et al (2020) and (Huang & Wang, 2019), although prosthetics on implants are clinically and scientifically consolidated, some challenges indicate the need for analysis and studies, since numerous technical and biological complications are common, such as screw loosening, porcelain cover fracture and bone loss. Aiming to understand these occurrences, this study evaluated, by means of three-dimensional finite element analysis (FEM), the biomechanical behavior of abutments, screws and bone in the face of a malpositioned implant in a single implant in the posterior region of the mandible, using as null hypothesis the non-increase of stresses in the evaluated elements.…”
Section: Introductionmentioning
confidence: 99%
“…In some clinical scenarios, where the implant placement can be limited by anatomical conditions (e.g., either bone deficiencies, the presence of anatomical structures or both, posterior edentulous area) and complex dental treatments are required (e.g., surgical procedures) which may lead to different complications and morbidity as well as increasing costs, the use of fixed dental prostheses with cantilever extensions that allow a more straightforward rehabilitation of these edentulous areas, still remains a long-term reliable treatment option with potent clinical, radiographic and aesthetic outcomes [ 6 ]. In a complex study, Schmid and co-workers [ 7 ] demonstrated the reliability of long-term treatment of implant-supported fixed dental prostheses with cantilever extension (FDPCs) by investigating the clinical and radiographic outcomes of implant-supported FDPCs with a cantilever extension of one premolar unit in posterior areas after a function time of more than 10 years. A 96.2% survival rate was noted of implants supporting FDPCs in posterior areas of maxilla and mandible with minimal marginal bone level changes, while the loss of retention, which represented the most frequent complication, was observed in 34.6% of patients.…”
Section: Introductionmentioning
confidence: 99%